Kualiti hidup dan harapan masa depan ibu tunggal melayu muslim di Pantai Timur Malaysia - Wan Ibrahim Wan Ahmad,; Zainab Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2010)
This study seeks to analyze the quality of life of single Malay Muslim mothers in East Coast Malaysia. Using a convenience sampling technique, a total of 500 single Malay Muslim mothers residing in Kelantan, Terengganu and Pahang were selected. The study employs both quantitative and qualitative methods to collect data. Major data for the quantitative analysis are derived from face-to-face interviews. Data of this study demonstrate that the average age of the respondents is 44.5 years old. Most of them become single mothers because of the death of their spouses, and only completed their education at primary school level. On a whole the study reveals that the level of quality of life of most of the single mothers is quite high. The study concludes that although these single mothers are facing various problems in daily life, but these problems do not affect their quality of life.